Penerapan Metode Human Resource Scorecard (HRSC) dan Analytical Hierarchy Process (AHP) dalam Penilaian Kinerja Karyawan pada PT. Laundry Kotak Indonesia Kanwil Pekanbaru - Pangestu, Bima Okta; Kusumanto, Ismu; Lubis, Fitriani Surayya; Yola, Melfa (Fakultas Teknik Universitas Tulang Bawang, 2026)
The rapid population growth in urban areas has increased the demand for Laundry services. PT. Laundry Kotak Indonesia, Pekanbaru Branch, plays a key role in managing and developing its workforce to ensure efficient operations and quality customer service. However, issues such as tardiness, safety negligence, lack of skills, and high employee turnover have negatively affected employee performance and overall productivity. Despite these challenges, no formal performance measurement system for employees has been implemented. This study aims to evaluate employee performance using the Human Resource Scorecard (HRSC) and Analytical Hierarchy Process (AHP) methods. The objective is to improve employee performance to support the company’s vision and competitiveness. The findings identify 14 strategic performance indicators, with the Financial perspective receiving the highest weight (0.437), providing a basis for more focused HR strategies, policy development, training resource allocation, and continuous performance evaluation. Keywords:, AHP, HRSC, Employee Performance Measurement, Performance